The localisation and micro-mapping of copper and other trace elements in breast tumours using a synchrotron micro-XRF system. - Farquharson, M; Geraki, K; Falkenberg, G; Leek, R; Harris, A (2007)
Trace elements have critical roles in cancer biology. The quantity and distribution of the elements Cl, Ca, K, P, S, Ti, Fe, Cu and Zn in samples of primary breast cancer have been assessed. The samples were formalin fixed tissue specimens formatted as microarrays of cores 1.0 mm diameter and 10 microm thick each. The data were obtained using a synchrotron X-ray fluorescence microprobe system. The spatial resolution of elemental maps was approximately 20 microm. Maps were compared with light transmission images of the samples and then the images were stained for cancer. The synchrotron system proved successful in producing data that could be mapped into high-resolution images where clear structure could be identified. Correlation of these distributions with the concentrations of cancer cells was achieved in some samples.